The Effect of Profopol In Prevention of Postoperative Nause And Vomiting (Ponv) in Post-Operating Patients With General Anesthesia at The Islamic Hospital (Rsi) Siti Rahmah Padang - Yenni Elfira (PT. Anagata Sembagi Education, 2024)
The incidence of postoperative nausea and vomiting is around 20-30% in patients undergoing general surgery and 70-80% in patients classified as high risk. The aim is to determine the effect of administering profopol in preventing Postoperative Nausea and Vomiting (PONV) in post-operative patients under general anesthesia. Data collection was carried out on 19 February 2024 - 22 March 2024. This type of quantitative research used a Quasi-experimental method with a Post Test Only Non-Equivalent Control Group research design. Using purposive sampling technique with 40 respondents, divided into 20 control groups and 20 intervention groups. Data analysis used the Mann-Whitney statistical test. The results of the intervention group research: 1 (5%) of 20 respondents experienced nausea and vomiting, 19 (95%) of 20 respondents did not experience nausea and vomiting, while in the control group 16 (80%) of 20 respondents experienced nausea and vomiting, 4 (20%) Of the 20 respondents, nausea and vomiting did not occur. The results of the Mann-Whitney statistical test showed a significant value of p 0.000 (p<0.005). Based on the conclusions from the research results, there is an effect of giving PROFOL in preventing PONV in post-operative patients under general anesthesia